An Analysis of Women, Education and Minangkabau Songket - Zamil, Ilham; Ezriani, Ezriani; Efi, Agusti; Budiwirman, Budiwirman (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
This study aims to describe the woman and education ​​in Minangkabau songket. Songket cloth is a sacred cultural object for the Minangkabau people. Besides showing the existence of culture, songket cloth is also not just anyone who is allowed to wear it. However, songket cloth is starting to be converted by the community. Songket cloth is not only used by datuak and bundo kanduang in Minangkabau traditional ceremonies. But it is also used for various non-sacred events, including attending birthday shows, farewell events between students at schools, graduation ceremonies, khatam qur'an, and is also used for wallets where money is kept, room interior decoration, souvenirs/souvenirs, as sandals, school bags, as car accessories, uniforms for stand keepers in performances such as exhibitions, bazaars and other trade missions, as ethnic identity in a performance in another cultural sphere. However, not many people know about how the birth process and the value of a piece of Minangkabau songket cloth. Interview methods and literature studies are used as data collectors to describe the processes and values ​​in Minangkabau songket.